2017
DOI: 10.1002/chir.22709
|View full text |Cite
|
Sign up to set email alerts
|

The inexpensive additive N‐methylmorpholine effectively decreases the equivalents of nucleophiles in the catalytic highly enantioselective arylation of aryl aldehydes

Abstract: Highly enantioselective arylation of aryl aldehydes catalyzed by (S)-H -BINOL-Ti(Oi-Pr) complex in the presence of N-methylmorpholine (NMM) as an effective and inexpensive additive is described for the first time. We found high enantioselectivity and yield but successfully reduced the equivalents of nucleophiles triarylaluminums by 50% compared with our previous report. The practicability of the process was thereby greatly increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…However, enantioselective reduction of aryl heteroaryl ketones in the presence of biocatalyst is still challenging. [25][26][27][28][29][30] There are a number of studies in the literature that contain cyclohexyl(phenyl) methanone 1 in high enantiomeric selectivity using chemical catalysts [31][32][33][34] ; however, there are very limited studies involving reduction of this compound using biocatalyst, and in these examples, the corresponding chiral secondary alcohols were obtained by low enantiomeric excess (ee) and conversion. 14,15 Biocatalysts have many superiorities compared with classic chemical catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…However, enantioselective reduction of aryl heteroaryl ketones in the presence of biocatalyst is still challenging. [25][26][27][28][29][30] There are a number of studies in the literature that contain cyclohexyl(phenyl) methanone 1 in high enantiomeric selectivity using chemical catalysts [31][32][33][34] ; however, there are very limited studies involving reduction of this compound using biocatalyst, and in these examples, the corresponding chiral secondary alcohols were obtained by low enantiomeric excess (ee) and conversion. 14,15 Biocatalysts have many superiorities compared with classic chemical catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In order to test the role of the magnesium additive, other magnesium salts were evaluated. When MgBr 2 and MgCl 2 was respectively added the reaction as additive, the adduct ee dramatically decrease (entries [26][27]. Considering Grignard reagent acitivity, n-BuMgCl was replaced with n-BuMgBr, resulted in noticeable decreases in enantioselectivity (entry 28).…”
Section: Resultsmentioning
confidence: 99%
“…The groups of Harada, Xu, and Yus utilized superstoichiometric Ti (O i ‐Pr) 4 to transmetallate RMgX (Br, Cl) to less reactive R‐Ti (O i ‐Pr) 3 , and then R‐Ti (O i ‐Pr) 3 highly enantioselectively delivered R group to aldehydes catalyzed by chiral diol‐Ti (O i ‐Pr) 2 complexes. Our group demonstrated that the additive bis([2‐[ N,N ′‐dimethylamino)]thyl) ether (BDMAEE) effectively deactivated the reactivity of Grignard reagents and then similarly transmetallated R functional group of RMgBr to R‐Ti (O i ‐Pr) 3 by using stoichiometric Ti (O i ‐Pr) 4 . The complex of chiral BINOL‐Ti (O i ‐OPr) 2 or H 8 ‐BINOL‐Ti (O i ‐OPr) 2 highly catalyzed the enantioselective delivery of R group to aldehydes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical rotation was determined with a Bellingham + Stanley, ADP220, 589‐nm polarimeter (Bellingham & Stanley Ltd, Tunbridge Wells, United Kingdom). ( S )‐Phenyl(thiophen‐2‐yl)methanol : white solid, mp 50–52°C, 1 H‐NMR (400 MHz, CDCl 3 ) δ = 7.47–7.26 (m, 6H), 6.96–6.88 (m, 2H), 6.06 (d, J = 3.9 Hz, 1H), 2.42 (d, J = 3.9 Hz, 1H (OH)); 13 C‐NMR (100 MHz, CDCl 3 ) δ = 148.1, 143.1, 128.5, 128.0, 126.4, 126.3, 125.4, 124.9, 72.4 (Fig. S1); [α] D 25 = 28.1 (c 1, CHCl 3 ), >99% ee; HPLC, Chiralcel OD‐H column, hexane/ i ‐PrOH, 98:2, flow rate of 0.8 mL/min, 220 nm, t R ( S ) 16.8 min (Fig.…”
Section: Methodsmentioning
confidence: 99%